Long-term Results of Conservative Treatment, Excision Arthroplasty and Triple Pelvic Osteotomy for the Treatment of Hip Dysplasia in the Immature Dog - Planté, J.; Dupuis, J.; Beauregard, G.; Bonneau, N. H.; Breton, L. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The efficiency of conservative treatment, excision arthroplasty of the femoral head and neck and triple pelvic osteotomy for the treatment of hip dysplasia in the immature dog were compared using locomotor, physical and radiographic examinations and owner’s evaluation. Cases selected for this study were dogs diagnosed with bilateral hip dysplasia, initially admitted with clinical signs (lameness, pain), immature at the beginning of the treatment (less than 12 months of age), with both hips subjected to the same treatment (conservative treatment, excision arthroplasty of the femoral head and neck or triple pelvic osteotomy). These dogs never showed any musculoskeletal problems other than hip dysplasia and the surgical treatment had been completed at least 20 months prior to re-evaluation time. Fourteen hips were re-evaluated in the conservative group, 16 in the triple pelvic osteotomy group and ten in the excision arthroplasty group. Locomotor, physical and owner’s evaluations demonstrated the superiority of the triple pelvic osteotomy. These evaluations also showed that excision arthroplasty was more efficient than conservative treatment. Radiographic examination demonstrated the obvious superiority of the triple pelvic osteotomy over conservative treatment.Locomotor, physical and owner’s evaluations demonstrated the superiority of the triple pelvic osteotomy over conservative treatment and excision arthroplasty for the treatment of hip dysplasia in the immature dog. Radiographic examination demonstrated the obvious superiority of the triple pelvic osteotomy over conservative treatment for joint congruence and control of degenerative joint disease.
Keywords: Canine hip dysplasia; dog; triple pelvic osteotomy; excision arthroplasty of the femoral head and neck